“I Felt Struggle but I Did It!”: EFL Pre-Service Teachers Struggles and Solutions During Digital Storytelling Creation to Promote Digital Literacy - Adiningrum, Lutfika Prasetyaning; Drajati, Nur Arifah; Sumardi (Institut Agama Islam Negeri Palopo, 2025)
In today's education landscape, many educators still struggle with utilizing technology, and educators are required to be digitally literate to use technology effectively. One innovative teaching method that can promote digital literacy is digital storytelling. This study employs narrative inquiry to investigate the challenges and solutions of Indonesian EFL pre-service teachers when designing digital storytelling projects to promote digital literacy. Thirty-six Indonesian EFL pre-service teachers participated in the study, with data collected through narrative frames, interviews, and artifacts in the form of digital stories. This study used thematic analysis and revealed that most participants encountered difficulties crafting engaging story plots, time limitations, and integrating media components such as images and sound effects. There were four challenges found in this study including access to technological resources, collaborative discussions, and learning new skills. This study implies that students and teachers need to understand the technology and that technological proficiency and collaborative learning are important in overcoming obstacles in the digital era.